Animal words: usborne babies library - Tyler, Jenny; Stitt, Sue (Usborne London, 1989)
A lively picture word book to help very young children build their vocabulary. Playful illustrations combine with the simplest text, as children are introduced to zebras, lions, crocodiles and seals. Peep-through holes on every page will fascinate young readers.